2012
DOI: 10.1038/hr.2012.115
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing and its relation to oxidative stress in patients with hypertension

Abstract: An increase in reactive oxygen species has been implicated in the pathologies of hypertension. This study was designed to evaluate antioxidant activity in hypertensive patients and to assess the relationship between oxidative stress and exercise tolerance in hypertensive patients with mild left ventricular diastolic dysfunction (LVDD). A total of 42 patients, aged 51 ± 9 years, with a long history of hypertension and mild LVDD (mitral flow velocities-E/A o1, deceleration time of E 4220 ms, and preserved ejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Previous studies found that functional capacity in hypertensive patients is decreased [25][26][27]. Our results agree with these findings, and furthermore reveal the difference between the well treated, the untreated and the unsatisfactory treated hypertensive patients.…”
Section: Right-ventricular Mechanics and Exercise Capacitysupporting
confidence: 95%
See 1 more Smart Citation
“…Previous studies found that functional capacity in hypertensive patients is decreased [25][26][27]. Our results agree with these findings, and furthermore reveal the difference between the well treated, the untreated and the unsatisfactory treated hypertensive patients.…”
Section: Right-ventricular Mechanics and Exercise Capacitysupporting
confidence: 95%
“…Additionally, the interaction between LV and RV could be an important mechanism which explains the association between the right heart and functional capacity. Namely, investigators have already demonstrated the relationship between left-ventricular structure and function with functional capacity [25][26][27]35,36], as well as the strong correlation between left-ventricular and right-ventricular function achieved mostly through IVS [37], which could further connect the right heart function and peak oxygen consumption. The strength of the present study lies in the fact that we succeeded to show that right-ventricular function and right-ventricular myocardial deformation are associated with functional capacity independently of leftventricular remodeling.…”
Section: Right-ventricular Mechanics and Exercise Capacitymentioning
confidence: 97%
“…Namely, Bruning et al 26 and Cockcroft et al 27 found no difference in endothelium-dependent vasodilator microvasculature responses between arterial hypertensive patients and normotensive individuals, whereas other studies revealed impaired endothelium-dependent relaxation in microcirculation in arterial hypertensive patients due to oxidative stress. 3,4,18,28 The impairment of endothelium-dependent relaxation in arterial hypertensive patients could be the reason of increased peripheral resistance and the cause of significantly greater exercise-induced blood pressure elevation in arterial hypertensive patients. Furthermore, increased systemic resistance leads to a reduction in cardiac output, which could be an additional cause of decreased oxygen uptake and reduced functional capacity in the hypertensive population.…”
Section: Systemic Circulation and Exercise In Arterial Hypertensionmentioning
confidence: 99%
“…3,4,20,33,36 The cornerstone of the relationship between the left ventricle and functional capacity is myocardial perfusion reserve, which is significantly reduced in arterial hypertension patients. 29 On the other hand, some authors have claimed that myocardial oxygen consumption is even increased in arterial hypertension patients without left ventricular hypertrophy, but normal in arterial hypertension patients with hypertrophy.…”
Section: Impact Of Left Ventricle On Exercise Capacity In Arterial Hymentioning
confidence: 99%
See 1 more Smart Citation